CONVENTIONAL AND NON-CONVENTIONAL RISK FACTORS FOR PERIPHERAL ARTERIAL DISEASE IN WOMEN - Igor Spinei; Dragoș-Alexandru Lubaș; Dumitru Casian (Arta Medica)
Objectives. To conduct a scoping review of the scientific literature summarizing current knowledge regarding gender-related differences in conventional and the impact of non-conventional risk factors for peripheral arterial disease (PAD) in women.